PPENGUJIAN “EFFICIENT MARKET HYPOTESIS” TERHADAP PERISTIWA “RIGHT ISSUE” DI BURSA EFEK JAKARTA di Bursa Efek Jakarta - U. Maman Rubaman (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2005)
Research try to test whether/what capital market of Indonesia specially Effect Exchange efficient to Jakarta in a condition form semi strength semistrong eftciient market. This research use data 10 company conductin go public during year period 2003. Research result indicate that there are. difference which signifikan amon price of share that happened in stock at the price of theoretical [is which ought to be happened by before and hereafter ex right date. While abnormal of return obtained by before and hereafter ex right date do not experience of difference which signifikan, variable of Price of share which, is mirrored by mean return accepted by a investor really able to live with to influence right issue. Abnormal average value of negative return show information spreading indication having the character of unsimmetrical